Harmoni Islam dalam Tradisi Tari Hadrah: Kearifan Lokal Masyarakat Gresik dalam Memelihara Kerukunan dan Toleransi Sosial - Alistiana, Lisa (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The Hadrah Dance tradition in Gresik Regency embodies a unique blend of Islamic values and local culture. Beyond serving as entertainment and cultural expression, Hadrah Dance conveys moral and spiritual messages. This study aims to reveal how the Hadrah Dance tradition reflects Islamic values and the local wisdom of the Gresik community in fostering social harmony and interfaith tolerance. Using a qualitative ethnographic approach, the research explores the meaning, function, and role of Hadrah Dance in Gresik society. Data collection was conducted through direct observation of Hadrah performances and interviews with artists, religious leaders, and local residents. Findings indicate that Hadrah Dance acts as an effective medium for Islamic teachings, promoting values of brotherhood, peace, and respect for diversity. Additionally, it strengthens social bonds among Gresik residents of diverse religious backgrounds, symbolizing a harmonious blend of local culture and Islamic teachings. The study concludes that the Hadrah Dance tradition holds significant value in maintaining social harmony and tolerance within a multicultural society, underscoring its importance for sustaining social cohesion in an increasingly diverse modern era.